PENERAPAN PENYUSUNAN LAPORAN DENGAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL DAN MENENGAH (SAK-EMKM): Studi Pada Toko Oleh-Oleh Pak Dj - Arsa Arsa; Muhammad Ismail; Ferri Saputra Tanjung; Muhamad Syawal (Al Dzahab: Journal of Economics, Management, Business and Accounting, 2022)
Purpose : This study aims to determine the application of the preparation of reports with financial accounting standards for micro, small and medium entities at Pak DJ's Souvenir Shop. The problems discussed in this study are how to prepare the financial statements of Pak DJ's gift shop and how to form the preparation of the DJ's gift shop's financial statements in accordance with SAK EMKM. The purpose of this study is to analyze the form of the financial statements of Pak DJ's Souvenir Shop and make a financial report of Pak DJ's Souvenir Shop in accordance with SAK EMKM.Design/methodology/approach : To obtain the data, the authors used descriptive qualitative research, namely through interviews with the owner of the DJ's Souvenir Shop and documentation of documents related to the preparation of the DJ's souvenir shop's financial statements.Findings : The results showed that the financial statements prepared by Mr. DJ's Souvenir Shop were only simple notes, namely cash receipts and disbursements, the application of financial statement preparation based on Financial Accounting Standards for Micro, Small and Medium Entities at Mr. DJ's Souvenir Shops compiled by researchers consisting of: from the statement of financial position, income statement and notes to financial statements.Research imlications : Statement of financial position with total assets of Rp. 101,832,700 and total liabilities and equity of Rp. 149,490,100, income statement with total profit of Rp. 99,490,100 and notes to financial statements.